A Genetics-First Approach Revealed Monogenic Disorders in Patients With ARM and VACTERL Anomalies - van de Putte, Romy; Dworschak, Gabriel C.; Brosens, Erwin; Reutter, Heiko M.; Marcelis, Carlo L. M.; Acuna-Hidalgo, Rocio; Kurtas, Nehir E.; Steehouwer, Marloes; Dunwoodie, Sally L.; Schmiedeke, Eberhard; Märzheuser, Stefanie; Schwarzer, Nicole; et al. (Frontiers in Pediatrics, 2020)
Background: The VATER/VACTERL association (VACTERL) is defined as the non-random occurrence of the following congenital anomalies: Vertebral, Anal, Cardiac, Tracheal-Esophageal, Renal, and Limb anomalies. As no unequivocal candidate gene has been identified yet, patients are diagnosed phenotypically. The aims of this study were to identify patients with monogenic disorders using a genetics-first approach, and to study whether variants in candidate genes are involved in the etiology of VACTERL or the individual features of VACTERL: Anorectal malformation (ARM) or esophageal atresia with or without trachea-esophageal fistula (EA/TEF). Methods: Using molecular inversion probes, a candidate gene panel of 56 genes was sequenced in three patient groups: VACTERL (n=211), ARM (n=204), and EA/TEF (n=95). Loss-of-function (LoF) and additional likely pathogenic missense variants, were prioritized and validated using Sanger sequencing. Validated variants were tested for segregation and patients were clinically re-evaluated. Results: In 7 out of the 505 patients (1.4%), pathogenic or likely pathogenic variants were identified in SALL1, SALL4, and MID1, genes that are associated with Townes-Brocks, Duane-radial-ray, and Opitz-G/BBB syndrome. These syndromes always include ARM or EA/TEF, in combination with at least two other VACTERL features. We did not identify LoF variants in the remaining candidate genes. Conclusions: None of the other candidate genes were identified as novel unequivocal disease genes for VACTERL. However, a genetics-first approach allowed refinement of the clinical diagnosis in seven patients, in whom an alternative molecular-based diagnosis was found with important implications for the counseling of the families.